Expert System Troubleshooting Shortest Route Finding Using Traveling Salesman Problem (TSP) - Rika Widya Perdana (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
The search for the shortest route is a path that is very functional in helping human activities. The Traveling Salesman Problem (TSP) is a method of finding the shortest route that a salesman can take when they want to visit several cities without having to visit the same city more than once. The case of Route Selection plays an important role because it must be on time and choose the alternative with the smallest value to the destination. Problems that occur in the form of lack of information and logic to obtain efficient information. The aim of this research is to minimize the distance. The search for a solution to the problem is to combine each distance taken to get to a place so that the Salesman can choose the Smallest alternative. The alternative mileage that has the smallest value is STRU, USTR, and URTS with an alternative value of 18.